The implementation of Türkiye's nuclear energy policy - Ahmet Alptekin Duru (Energy Strategy Reviews)
This study analyzes the adoption and implementation of Türkiye's nuclear energy policy. Türkiye entered the nuclear energy league via the build-own-operate scheme, which has impeded the country's goals of technological development and national industry growth. The country has focused on ensuring electricity supply rather than long-term energy independence via technology transfer. For Türkiye, using nuclear power is a viable and reasonable strategy to solve the problems of future electricity demand, energy independence, and greenhouse gas emission reduction. The country may modify its technical and managerial capabilities to construct and operate NPPs with the support of a supplier country; however, it has lacked political commitment. International experience shows that a comprehensive government-led know-how transfer program based on build-operate-transfer scheme can be successful in Türkiye.